2019
DOI: 10.3390/en12224317
|View full text |Cite
|
Sign up to set email alerts
|

Demand Price Elasticity of Residential Electricity Consumers with Zonal Tariff Settlement Based on Their Load Profiles

Abstract: The concept of price elasticity of demand has been widely used for the assessment of the consumers’ behavior in the electricity market. As the residential consumers represent a significant percentage of the total load, price elasticity of their demand may be used to design desirable demand side response programs in order to manage peak load in a power system. The method presented in this study proposes an alternative approach towards price elasticity determination for zonal tariff users, based on comparisons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…The user should not be encouraged to contribute to the system's efficacy. If real-time pricing is introduced, the price will become elastic on the demand side instead of the fixed price tariff [11]. From the other direction, the supply curve would also be reshaped by an increased number of renewables.…”
Section: Review On Dsmmentioning
confidence: 99%
“…The user should not be encouraged to contribute to the system's efficacy. If real-time pricing is introduced, the price will become elastic on the demand side instead of the fixed price tariff [11]. From the other direction, the supply curve would also be reshaped by an increased number of renewables.…”
Section: Review On Dsmmentioning
confidence: 99%
“…The researcher found that the stock of appliances is the main variable that will determine the electricity demand in India. With almost the same spirit, Andruszkiewicz et al (2019) proposes an alternative estimation model for electricity demand in Poland. Researchers found that electricity demand is still an essential part of European household needs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whereas the short-term price elasticity of electricity demand has historically been very low, a number of newer research papers find significant elasticities in some power markets. The reference Andruszkiewicz et al (2019) provides a survey of shortterm elasticities found in the academic literature, with annual values below −0.5 for Switzerland, Portugal, US and China. Also, the authors argue that elasticities are likely to increase with the introduction of smart metering and time-of-use tariffs.…”
Section: Literature Reviewmentioning
confidence: 99%